58.4k views
4 votes
What is the answer to 3(4g+6)=2(6g+9)

User VoidStern
by
5.4k points

2 Answers

0 votes

Answer:

Solution: All real numbers.

Explanation:


3(4g+6)=2(6g+9)\qquad|\text{use distributive property}\\\\(3)(4g)+(3)(6)=(2)(6g)+(2)(9)\\\\12g+18=12g+18\qquad|\text{subtract 12g from both sides}\\\\18=18\qquad TRUE

It's an identity equation.

User Skawful
by
5.4k points
2 votes
use the distributive property to get 12g+18=12g+18
since both sides equal each other, your answer is 0=0 & its an identity :)
User Sunny Kumar Aditya
by
5.5k points